ANALISIS MAQASHID SYARIAH TERHADAP PENETAPAN ITSBAT NIKAH BAGI SUAMI YANG TELAH MENINGGAL DUNIA (STUDI KASUS PENETAPAN HAKIM PENGADILAN AGAMA BULUKUMBA NOMOR 64/Pdt.P/2020/PA.Blk) - Ummul Khaerah; Ibnu Izzah (Universitas Islam Negeri Alauddin Makassar, 2022)
The main problem of this research is the Maqashid Syariah Analysis of the Determination of Itsbat Marriage for Husbands Who Have Died (Case Study of Determination of Judges at the Bulukumba Religious Court Number 64/Pdt.P/2020/PA.Blk). The sub-problem is, how is the process and consideration of the judge in determining the marriage itsbat for the husband who has died in case number 64/Pdt.P/2020/PA.Blk then the determination of the marriage itsbat for the husband who has died is associated with maqashid sharia, type The research used is qualitative research using normative theological (syar'i) and juridical normative research approaches. The results of this study, namely, the judge in determining the marriage certificate in case number 64/Pdt.P/2020/PA.Blk was only carried out in 1 trial where the judge in determining the application saw the facts given by the witness, the applicant also has submitted authentic letter evidence in the form of, a photocopy of a family card, a photocopy of a death certificate, and also a photocopy of a decision letter from PT. Tri Tunggal Sentra Buana, the judge referred to the book I'anatut Juz IV pages 253-254 and the book Bughyatul Mustarsyidin page 298, in addition to Law Number 23 of 2006 concerning Population Administration as amended by Law Number 24 of 2013 jo. Article 7 paragraph (1) KHI. The determination of itsbat marriage case number 64/Pdt/P/2020/PA.Blk is associated with maqashid sharia, which is included in the category of Ad-dharuriyyat and hajiyyat which the judge looks at the benefit; to preserve life/soul; to maintain offspring; and to protect property. The implication of this research is to provide information to the public that how important it is that marriage is registered, if the marriage is not registered it can be overcome by submitting an application for itsbat marriage at the local Religious Court, the judiciary in deciding/establishing a decision/application must pay more attention to the benefit of justice seekers , the KUA institution in order to provide advice, direction and also socialization to the community to register marriages at the Marriage Registrar (PPN), so that both parties and their descendants get legal certainty. Keywords: Maqashid Sharia, Itsbat Marriage, Die.